Thinking Outside the (Pine) Box: Ethics Consultation as Imaginative Inquiry and Practical Problem-Solving. - Bartlett, Virginia L. (American Journal of Bioethics, 2026)
The article explores the ethical dilemma faced by a social worker regarding the cremation of a deceased individual at a hospital's expense, emphasizing that the answer to whether this is permissible is complex and context-dependent. It highlights the need for a thorough understanding of both practical and moral considerations, including financial constraints, legal definitions of "unclaimed" bodies, and the emotional and cultural beliefs of the widow regarding burial versus cremation. The author suggests that effective communication and collaboration among stakeholders, including the widow and hospital staff, are crucial in navigating this sensitive situation, ultimately advocating for a nuanced approach to ethics in clinical practice.